Linking microbial functional gene abundance and soil extracellular enzyme activity: Implications for soil carbon dynamics - Chen, Ji; Sinsabaugh, Robert L. (Global change biology, 2021)
Emerging evidence indicates that enzyme‐catalyzed transformation and degradation of soil organic matter at the ecosystem scale is more likely driven by microbial functional gene abundance, rather than short term induction/repression responses. In this paper, we are trying to highlight the potential links between microbial functional gene abundance and soil extracellular enzyme activity. Those links will likely offer a new path for optimizing the model performance of microbial‐mediated soil C dynamics from microbial functional gene perspectives.